Developing a peer-led intervention to promote COVID-19 testing in low-income housing settings - Plunk, Andrew D.; Hannon, Kapri; Carver, Alexandra; Cooper, Diane; Grant, Debra; Greene, Sudie; Morgan, Emma; Gehlert, Sarah (Frontiers in Public Health, 2023)
Abstract Background: The Housing Collaborative project at Eastern Virginia Medical School has developed a method of adapting public health guidance from public housing communities, which face tremendous health challenges in cardiometabolic health, cancer, and other major health conditions. In this paper, we describe how academic and community partners in the Housing Collaborative came together to do this work with a focus on COVID-19 testing in the context of the emerging pandemic. Methods: The academic team used virtual community engagement methods to interact with the Housing Collaborative Community Advisory Board (HCCAB) and a separate cohort of research participants (N = 102) recruited into a study of distrust in COVID-19 guidance. We conducted a series of 44 focus group interviews with participants on related topics. Results from these interviews were discussed with the HCCAB. We used the collaborative intervention planning framework to inform adaptation of public health guidance on COVID-19 testing delivered in low-income housing settings by including all relevant perspectives. Results: Participants reported several important barriers to COVID-19 testing related to distrust in the tests and those administering them. Distrust in housing authorities and how they might misuse positive test results seemed to further undermine decision making about COVID-19 testing. Pain associated with testing was also a concern. To address these concerns, a peer-led testing intervention was proposed by the Housing Collaborative. A second round of focus group interviews was then conducted, in which participants reported their approval of the proposed intervention. Conclusions: Although the COVID-19 pandemic was not our initial focus, we were able to identify a number of barriers to COVID-19 testing in low-income housing settings that can be addressed with adapted public health guidance. We struck a balance between community input and scientific rigor and obtained high quality, honest feedback to inform evidence-based recommendations to guide decisions about health.